BEZROBOCIE JAKO CZYNNIK KSZTAŁTUJĄCY WSKAŹNIKI PRZESTĘPCZOŚCI - Szczepaniec, Maria (Zeszyty Prawnicze, 2016)
UNEMPLOYMENT: A FACTOR IMPACTING ON CRIME RATE Summary The article presents the correlation between unemployment and crime. The main research issue in the present article is the hypothesis that unemployment is a factor determining criminal behaviour. The article presents empirical research which shows that unemployment may affect crime rate in various ways. Sometimes unemployment may lower crime rate, but there are also situations when it raises the crime rate.